Breaking symmetry: effects of habitat disturbance on flight-related traits of two Triatominae species - Fiad, Federico G.; Nattero, Julieta; Cardozo, Miriam; Gigena, Gisel V.; López, Ana; Carezzano, Fernando; Gorla, David E.; Rodríguez, Claudia S. (Frontiers in Insect Science, 2025)
IntroductiomHabitat fragmentation alters environmental structure and imposes selective pressures on dispersal-related traits in insect vectors, potentially driving morphological adaptations that enhance flight performance. In this study, weinvestigate how landscape metrics influence the size and shape of the head and wings in two Triatominae species, Triatoma garciabesi and T. guasayana, which present differing ecological strategies. We hypothesize that individuals from more fragmented landscapes exhibit phenotypic shifts associated with enhanced dispersal capacity and increased morphological symmetry.MethodsTo test this, we combined community-based sampling of triatomines with geometric morphometrics and multiscale landscape metrics. We applied geometric morphometrics and generalized linear models (GLM)-based analyses to assess the effects of habitat fragmentation on flight-related morphology.ResultsOur results reveal that T. garciabesi shows increased head asymmetry and narrower wings in highly fragmented landscapes, while T. guasayana exhibits subtle shifts in head shape asymmetry and greater sexual dimorphism. In both species, head and wing sizes tended to be larger in fragmented habitats, especially in females, suggesting differential morphological responses that may reflect species-specific dispersal strategies.DiscussionHabitat fragmentation differentially affects T. garciabesi and T. guasayana, leading to distinct dispersal syndromes. Triatoma garciabesi shows greater plasticity, highlighting the role of landscape structure in shaping adaptive dispersal traits.